Applications Introduction of Gondang Manis Guava on Android - Miftachul Chusnah; Anang Muzakki Yazid (AGARICUS: Advances Agriculture Science & Farming, 2022)
Gondang Manis guava is located in Bandarkedungmulyo District, Jombang Regency. This guava is one of the superior varieties of Guava. This fruit is a national superior fruit row. Therefore, an information system related to Gondang Gondang Manis is needed to provide information to the public starting from general information about Guava Gondang Manis, cultivation, and processed products of Guava Gondang Manis. By utilizing Android development, the public will easily access information about Guava Gondang Manis. The research location was conducted in the village of Gondang Manis, Bandarkedungmulyo district, Jombang regency. Primary data is data taken directly from the research location in Gondang Manis village, through direct observation at the location, interviews with the government, and community shops, and filling out questionnaires. The respondents who were selected were 15 people to fill out the research questionnaire as follows: Government (2 people), namely the village head and apparatus, Jombang Agricultural Service Employees (1 person), Community Shop (2 people), and the main actors (10 people). Secondary data is data obtained through agencies related to this research, both tabulated and descriptive. This application analysis method uses the Waterfall method. The Waterfall method is a device development step that uses sequential stages, with the process of completing its manufacture from top to bottom and flowing (like a waterfall) by going through the requirements, design, implementation, and maintenance phases. This application is made using Framwork7 and compiled using Cordova. This application has been tested on the community and got a score of 3,42 categorized as good. Keywords: Application; Andrroid; Gondang Manis Guava.